Innovation, efficiency and inclusion: Integration of digital technologies in the Indian microfinance sector - Saon Ray; Sandeep Paul; Smita Miglani (Indian Council for Research on International Economic Relations (ICRIER), 2018)
Digital technologies are rapidly making inroads into all realms of human life and the microfinance sector is one such area. Ongoing innovations in digital technology are contributing to reshaping its operational models, governance structures, its risk profile, industry networks and dominant practices. Innovation and integration of digital technology are both important because of their potential to promote development by spurring innovation, improving efficiency and increasing inclusion. This paper explores how these mechanisms - innovation, inclusion and efficiency - have been integral to microfinance operations in the past, and how innovations in digital technology may be yet another opportunity for microfinance institutions to promote development. We refer to examples from the Indian microfinance industry to explore how the digital technology changes are shaping the microfinance sector.
Keywords: E59; F39; G21; 330; Digital innovation; Digital technologies; Microfinance